Manhattan Project to the Santa Fe Institute : the memoirs of George A. Cowan - Cowan, G. A. (George A.), 1920-2012 (University of New Mexico Press, 2010)
"George Cowan's memoir is an engaging eyewitness account of how science works and how scientists, as people, work as well. In discussing his career in nuclear physics from the 1940s into the 1980s, Cowan talks about some of his assignments in nuclear forensics, including President Harry Truman's skeptical review of the analysis of Russia's first atomic bomb test in 1949. Throughout his book, Cowan weaves in intriguing anecdotes about a large cast of distinguished scientists - all related in his concise, wry manner."--Jacket